Corrosion and corrosion control. An introduction to corrosion science and ingineering - Winston Revie, R (Estados Unidos de América : Wiley-Interscience, 2008)
Apéndices
Índice alfabético
META
INGE
Keywords: Corrosión; Prevención; Corrosión de sólidos; Corrosión Atmosférica; Electroquímica; Temodinámica; Revestimientos; Medio Ambiente; libros